DAKWAH: SUATU PENDEKATAN KULTURAL - Ihsan, Muhammad Alim (State Institute of Islamic Studies (IAIN) Palu, 2008)
Inviting people to perform the good deeds is one of the Islamic core teachings. For this reason, a daâ€™wah should be delivered by employing a proper approach. In other words, a dÃ¢â€™i should notice the social and cultural condition of the people as the target of his daâ€™wah. Within this context, one of the approaches that can be employed in delivering a daâ€™wah is cultural approach. Employing this kind of approach, a dÃ¢â€™i will be able to promote the Islamic teaching as a social and cultural need of the Muslims. In addition, cultural approach is persuasive in nature, that is transforming the values of the Qurâ€™an and the prophetâ€™s tradition into ideas and deeds in the form of norms.Kata Kunci : dakwah,Â pendekatan kultural, penyebaran Islam